Magnetic resonance perfusion or fractional flow reserve in coronary disease - Nagel, Eike; Greenwood, John P; Steen, Henning (The New England journal of medicine, 2019)
In patients with stable angina, two strategies are often used to guide revascularization: one involves myocardial-perfusion cardiovascular magnetic resonance imaging (MRI), and the other involves invasive angiography and measurement of fractional flow reserve (FFR). Whether a cardiovascular MRI–based strategy is noninferior to an FFRbased strategy with respect to major adverse cardiac events has not been established. (...)
Gesehen am 09.01.2020